Efficacy and sublethal effects of imidacloprid on the survival and fecundity of Aulacophora Foveicollis (lucas) (Coleoptera Chrysomelidae) - Ibrahim Yusof, Rezali Izyan Nadirah, (N/A, 2014)
Efficacy and sublethal effects of imidacloprid on the survival and fecundity of Aulacophora Foveicollis (lucas) (Coleoptera Chrysomelidae) by Ibrahim Yusof, Rezali Izyan Nadirah,